IDENTIFYING WEAKNESSES IN READING LITERACY AMONG THE TOP-RANKING PRIMARY SCHOOL STUDENTS IN LITERATURE IN THE REPUBLIC OF SERBIA - Stakić, Mirjana M.; Mrkalj, Zona (Studies in Teaching and Education, 2025)
The results of international assessments, such as PIRLS (2021) and PISA (2022), indicate that primary school students in the Republic of Serbia achieve significantly lower results than the international average when it comes to advanced levels of reading literacy. Therefore, a study was conducted to identify weaknesses in the reading literacy of seventh- and eighth-grade students who achieve the best results in the field of literature. The sample included 410 students who participated in the 2024 National Literature Competition Literary Olympiad. In order to identify their weaknesses in reading literacy, the study was based on the following research tasks: 1. Determine the types of tasks used to assess reading literacy in the National Literature Test; and 2. Analyze students' success in solving these tasks. To achieve the first research task, a content analysis method was applied to the measuring instrument (official tests from the National Competition). Tasks were identified (five per grade level), followed by an analysis of content elements, task types, and specific learning outcomes related to reading literacy. To assess students’ success in solving these tasks, descriptive statistical measures and a nonparametric chi-square test were used. The obtained results show that final-year primary school students who excel in literature perform worse in understanding scientific and technical texts compared to literary texts, as well as in understanding literary texts whose context (historical, social) is unfamiliar to them. This finding has pedagogical implications, highlighting the importance of promoting various reading strategies and motivation as a predictor of reading literacy success.
Keywords: teaching methods of Serbian language and literature; reading motivation; text comprehension; reading strategies; reading literacy